2009
DOI: 10.1103/physrevb.80.245206
|View full text |Cite
|
Sign up to set email alerts
|

Theory of near-gap second harmonic generation in centrosymmetric magnetic semiconductors: Europium chalcogenides

Abstract: Second harmonic generation is strictly forbidden in centrosymmetric materials, within the electric dipole approximation. Recently, it was found that the centrosymmetric magnetic semiconductors EuTe and EuSe can generate near-gap second harmonics, if the system is submitted to an external magnetic field. Here, a theoretical model is presented, which well describes the observed phenomena. The model shows that second harmonic generation becomes efficient when the magnetic dipole oscillations between the band-edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
0
19
1
Order By: Relevance
“…We have shown that particular features of the crystallographic structure and the electronic band structure of the centrosymmetric EuTe allow crystallographic and magnetic-field-induced THG. In contrast to the SHG studies, 6,7,60 THG of electric dipole type was observed in zero magnetic field. The contained resonances were assigned to specific electronic transitions between the ground 4f 7 state at the top of the valence band and excited 4f 6 5d 1 states of the Eu 2+ ions, which form the lowest energy conduction band.…”
Section: Discussioncontrasting
confidence: 42%
See 4 more Smart Citations
“…We have shown that particular features of the crystallographic structure and the electronic band structure of the centrosymmetric EuTe allow crystallographic and magnetic-field-induced THG. In contrast to the SHG studies, 6,7,60 THG of electric dipole type was observed in zero magnetic field. The contained resonances were assigned to specific electronic transitions between the ground 4f 7 state at the top of the valence band and excited 4f 6 5d 1 states of the Eu 2+ ions, which form the lowest energy conduction band.…”
Section: Discussioncontrasting
confidence: 42%
“…60 We also assume T = 0 K, meaning that the unperturbed electronic system is in the ground state 4f 7 ͑ 8 S 7/2 ͒. We shall use two characteristics of the above described electronic energy level scheme: ͑i͒ the energy spread of the excited states is much smaller than the band gap, i.e., E G ӷ 4f and E G is much larger than the energy width of ⑀ X ͑k͒; ͑ii͒ all excited states have the same parity, which is opposite to the parity of the ground state.…”
Section: Discussion and A Quantum-mechanical Model Of Thgmentioning
confidence: 99%
See 3 more Smart Citations